Applications of thermoplastic - based blends - Ching, Y. C.; Chuah, C. H.; Ching, K. Y.; Abdullah, L.C.; Rahman, A. (Elsevier, 2017)
The properties of a thermoplastic blend depends on its constituent materials. Properties and applications vary for each thermoplastic blends, and a number of such materials have been fabricated in recent years. This review provides an in-depth discussion on the properties and applications of various thermoplastic blends. Recent works and articles are cited in this paper. These citations are ubiquitous in the development of thermoplastics blends and their applications.